PELAKSANAAN EKSTRAKURIKULER SENI TARI PASAMBAHAN DI SMP NEGERI 27 PADANG (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to describe the implementation of the Pasambahan Dance extracurricular activity at SMP Negeri 27 Padang. The type of research used is qualitative research with a descriptive method. The research object is the dance extracurricular activities, while the research subjects consist of the coach and 25 female students who are members of the dance extracurricular in grades VII and VIII at SMP Negeri 27 Padang. Data collection was carried out through observation, interviews, documentation, and literature studies. The data were analyzed through stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that the implementation of the Pasambahan Dance extracurricular at SMP Negeri 27 Padang has been carried out well through the stages of planning, implementation, and evaluation conducted systematically. The planning includes setting the training schedule, the content for the Pasambahan Kreasi Dance, learning methods, as well as supporting facilities and infrastructure. The activities are carried out once a week for five sessions using lectures, demonstrations, and peer tutoring methods. Evaluation is done by observing the students’ ability to master movement techniques, coordination, timing with the music, and the overall dance performance. This extracurricular activity has a positive impact on improving dance skills, discipline, responsibility, teamwork, as well as students’ appreciation of Minangkabau culture. Although there are still challenges such as limited facilities and infrastructure and not all students attend regularly, the activities can still run well thanks to the support from the school, coaches, and the students' enthusiasm.